Delayed-onset parkinsonism is common after isolated striatal infarcts - Holm, Hedda; Dietrichs, Espen; Joutsa, Juho; Connelly, James P.; Lund, Christian G.; Skjelland, Mona; Gundersen, Vidar; Bjerknes, Silje (Frontiers Media SA, 2026)
Background:
While case studies have suggested that only a minority of patients with putaminal lesions develop parkinsonism, existing data are limited by involvement of adjacent brain regions, brief follow-up period, and lack of systematic imaging. As a result, the true incidence and nature of parkinsonism following isolated striatal infarcts remain unknown. This study aimed to assess the incidence, timing, and clinical features of parkinsonism following isolated striatal infarcts using comprehensive imaging and longitudinal clinical assessments.
Methods:
We conducted a prospective cohort study at Oslo University Hospital, including patients treated with intravenous thrombolysis and/or mechanical thrombectomy for acute ischemic stroke resulting in isolated striatal infarcts. Patients with NIHSS scores of six or above were excluded to reduce the influence of other neurological deficits. Clinical evaluations included NIHSS, MDS-UPDRS, and MoCA scales at 3 months and 1 year. Brain MRI was performed at 3 months and [123I]FP-CIT SPECT imaging at 1 year to assess dopaminergic integrity.
Results:
Fifteen patients (median age 61) with unilateral striatal infarcts were included between June 2020 and January 2023. The median NIHSS score was one at both follow-ups. By 3 months, 27% (4/15) of patients developed parkinsonism, increasing to 67% (10/15) at 1 year. MDS-UPDRS motor scores showed a progressive increase over time, with contralateral akinetic-rigid symptoms predominating. Cognitive performance remained stable, with no significant changes in MoCA scores. Both the volume and location of the infarct appeared to influence the likelihood of developing motor symptoms. All patients showed reduced [123I]FP-CIT uptake in the infarcted striatum.
Conclusion:
This is the first study to systematically investigate delayed-onset parkinsonism in patients with isolated striatal infarcts, and our findings indicate that it may occur more frequently than previously recognized. These results challenge existing assumptions and highlight the potential value of repeated, targeted assessments in this population to improve detection and management of post-stroke parkinsonism.